Penerapan Hidroterapi dan Relaksasi Otot Progresif Pada Asuihan Keperawatan Lansia dengan Hipertensi - Rosmin, Meike Parobe; Manggasa, Dafrosia Darmi (Madago Nursing Journal, 2023)
The Causes Hypertension is a condition in which systolic and diastolic pressure increases beyond normal limits, an increase in blood pressure both systolic and diastolic with symptoms such as dizziness accompanied by a stiff neck, unable to sleep, aching bones, often tingling, and sometimes cold sweats. In dealing with the problem of increased blood pressure, namely by doing hydrotherapy and progressive muscle relaxation. The purpose of the study was to determine the application of hydrotherapy and progressive muscle relaxation to reducing blood pressure in nursing care for elderly people with hypertension in the Pandiri village. The research method is descriptive with a case study approach. Research Results: in the study the patient complained of dizziness and pain in the head to the back of the neck, the pain felt like stabbing, intermittent pain, blood pressure 160/100 mmHg, pulse 90x/minute, heart palpitations and difficulty getting to sleep and often waking up at night. Nursing diagnoses (1) risk of ineffective cerebral perfusion (2) Acute pain (3) Sleep pattern disturbance. Nursing interventions: monitoring of vital signs, pain management. Nursing implementation examines TTV, assesses the patient's pain scale, provides hydrotherapy and progressive muscle relaxation. Evaluation after nursing actions for 3 days the patient said the pain in the head to the nape was reduced, the patient looked relaxed, the patient's blood pressure was 130/80 mmHg, the patient was calm, the patient slept well. Conclusion: the application of hydrotherapy and progressive muscle relaxation can reduce blood pressure. Keywords: Elderly, Hypertension, Hydrotherapy, Progressive Muscle Relaxation